Effects of dietary quercetin on performance and cytochrome P450 expression of the cotton bollworm, Helicoverpa armigera. Issue 6 (6th October 2015) - Liu, D.; Yuan, Y.; Li, M.; Qiu, X.
Abstract: Quercetin is ubiquitous in terrestrial plants. The cotton bollworm Helicoverpa armigera as a highly polyphagous insect has caused severe crop losses. Until now, interactions between this pest and quercetin are poorly understood at the biochemical and molecular levels. In this study, we investigated the in vivo effects of quercetin on performance of cotton bollworm and on cytochrome P450 (P450) expression. Deleterious effects of quercetin on the performance of the cotton bollworm, including growth, survival, pupation and adult emergence were observed after oral administration of 3 and 10 mg g −1 quercetin to larvae since the third instar, whereas no significant toxic effect was found at 0.1 mg g −1 quercetin treatment. Piperonyl butoxide treatment enhanced the toxicity of quercetin. In vitro metabolism studies showed that quercetin was rapidly transformed by gut enzymes of fifth instar larvae of the cotton bollworm. qRT–PCR results revealed that the effect of quercetin on P450 expression was tissue- and dose-specific. Quercetin regulated P450 expression in a mild manner, and it could serve as P450 inducer (CYP337B1, CYP6B6) or repressor (CYP337B1, CYP6B7, CYP6B27, CYP9A14, CYP6AE11, and CYP4M7). These findings are important for advancing our understanding of the biochemical and molecular response of insects to plant toxins and have implications for a smart pest control.